The SWI/SNF complex is a mechanoregulated inhibitor of YAP and TAZ - Chang, Lei; Krijgsveld, Jeroen (Nature, 2018)
The ARID1A-containing SWI/SNF complex operates as an inhibitor of the pro-oncogenic transcriptional coactivators YAP and TAZ; this interaction is regulated by cellular mechanotransduction.
Gesehen am 09.04.2019